(untitled) (AYUSHDHARA, 2019)
The disease Hypothyroidism is more prevalent among Thyroid disorders. For giving proper Ayurvedic treatment to patient of Hypothyroidism, it is important to study this disease in the view of Ayurveda. In Ayurveda, there is no direct reference of the disease which can be correlated to Hypothyroidism. But, some of the signs and symptoms of Hypothyroidism are parallel to Kaphaj pandu and hence to see Correlation between them detailed study of Kaphaj pandu is also done. In present study To study correlation between Hypothyroidism and Charakokta kaphaj pandu, 30 diagnosed patients of Hypothyroidism were selected and a detail case taken of each patient to find out presence of number of Lakshanas of Charakokta kaphaj pandu in that patient. Presence of minimum 50% Lakshanas of Kaphaj pandu will be considered as positive result i.e., Hypothyroidism can be correlated with Charakokta kaphaj pandu. Out of 30 patients of Hypothyroidism 3 patients had more than 10 symptoms of Kaphaj pandu. Correlation between Hypothyroidism and Kaphaj pandu was made and expressed statistically. Out of 30 observed patients 3 patients were having more than 10 symptoms of Kaphaj pandu and remaining 27 patients were having symptoms of Kaphaj pandu. In these 30 patients it is seen that average TSH level is 23.13, which is high than normal level i.e. 5.5. Further, average HB was 8.7 which is below the normal range i.e., 12-14 gm/dl. As described earlier, Shwetavbhasata is one of the main symptoms of Kaphaj pandu and it is found in every patient.